KUASA PATRIARKI DALAM NOVEL GENDUK KARYA SUNDARI MARDJUKI - Tri Lestari; Muamar Abd. Halil; Hubbi Saufan Hilmi (Kantor Bahasa Provinsi Maluku Utara, 2021)
This study aims to describe the forms of patriarchal power in the novel Genduk by Sundari Mardjuki. This research is a qualitative descriptive research. The data in this study are the forms of patriarchal power in the Genduk novel, while the data sources in this study are primary data, namely the novel Genduk by Sundari Mardjuki and secondary data sources in the form of theoretical books and relevant research articles. The data collection technique used in this research is document analysis technique. Analysis of the data in this study using interactive analysis with feminism studies. The results of this study indicate that there are several forms of patriarchal power in the novel Genduk by Sundari Mardjuki in the form of subordination, stereotypes, marginalization of women, workload, physical violence against women.